(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article reveals that the multi-party system is an important factor in ensuring the diversity of opinions in the society and democratization of the country. The role and importance of the multi-party system in ensuring the rule of law and social justice in the society was discussed. It was highlighted that the development of a healthy competition system between parties serves as an important factor in ensuring the diversity of opinions and the rule of law in society.At the same time, this article talks about the importance of political parties, which are an important institution of civil society, in improving the political culture of citizens. Organization, goals and programs of political parties operating in our country are analyzed.